Impact of Environmental Tax Collection on CO2 Emission in Vietnam - Thi, Hoa Dinh; Vu Thi, Kim Anh; Phuong, Duyen Ly; Thu, Van Pham; Minh, Chau Hoang Thi (International Journal of Energy Economics and Policy, 2020)
Studying the impact of environmental tax collection on the amount of CO2 emissions in Vietnam; then, assessing the impact of environmental tax collection on envirommental protection, CO2 emission reduction facing to the climate change in Vietnam. In this paper, the data are collected from 2001 to 2018 at General Statistics Office, General Department of Taxation of Vietnam, World Bank, and related researches of scholars. The data collected include: the amount of CO2 emissions of Vietnam, the environmental tax collection, the amount of natural resource consumption tax collection, the amount of excise tax and total population of Vietnam. The research result shows that the amount of environmental tax collection has strong and negative impact on the amount of CO2 emissions. Keywords: CO2, emission, environmental tax, excise tax, population, Vietnam JEL Classifications: Q32, Q43, E62 DOI: https://doi.org/10.32479/ijeep.10153